Stability study and degradation kinetics of ceftazidime in pharmaceutical preparations - Moreno, Andréia de Haro [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Scientific & Academic Publishing, 2012)
Stability study of ceftazidime was realized in order to investigate kinetics of degradation of this drug both in powder for injection and reconstituted sample. Ceftazidime was submitted to conditions of accelerated thermal degradation and photodegradation. Analyses of the degraded samples were performed by microbiological assay and decomposition reactions could be described by zero-order and second-order kinetics. Results obtained confirm the reliability of the microbiological assay for determination of ceftazidime by the presence of its degradation products. The present study revealed thermal and photo lability of the drug, especially as reconstituted sample, and protection is recommended during storage and handling.
Keywords: Ceftazidime; Stability studies; Degradation kinetics